(untitled) (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2023)
Learning Devices are substantive elements in the learning process. However, based on the results of interviews and observations in the field, it was found that teachers needed the skills to make a plan that became a reference in implementing teaching and learning activities. By the rules of the 2013 curriculum, IAIN Palangkaraya, which has a Tarbiyah Department, feels compelled to share knowledge in the field of curriculum and respond by carrying out community service activities to answer problems related to learning tools. This training aims to improve teachers’ professionalism as professionals at the Integrated Islamic Elementary School (SD-IT) Hasanka Boarding School Palangkaraya. Increase teachers’ understanding and knowledge of the preparation of learning tools for the 2013 curriculum at SD-IT and enhance the ability of teachers to develop curriculum learning tools appropriately and apply them to learning at SD-IT Hasankan Boarding School Palangka Raya; there is planning for implementing learning by the field of study refers to the 2013 curriculum principles to be applied in classroom learning. This service activity uses the service method with several stages: inculturation, discovery, defined design, and reflection. The result of this activity is to produce learning tools that have been made by teachers during the training and mentoring process in the form of Learning Implementation Plans (RPP), Semester Programs (Prosem), and Annual Programs (Prota) referring to the 2013 curriculum principles and can be implemented in teaching and learning activities in each class. — Perangkat Pembelajaran merupakan unsur yang substantive dalam proses pembeljaran. Namun dilapangan berdasarkan hasil wawancara dan observasi masih ditemukan guru belum memiliki keterampilan dalam membuat sebuah perencanaan yang menjadi acuan dalam pelaksanaan kegiatan belajar mengajar. sesuai dengan kaidah kurikulum 2013, IAIN Palangkaraya yang memiliki Jurusan Tarbiyah merasa terpanggil untuk berbagi keilmuan dibidang kurikulum dan menyikapi dengan melakukan kegiatan pengabdian masyarakat untuk menjawab permasalahan berkaitan dengan perangkat Pembelajaran. Tujuan Pelatihan ini yaitu guru sebagai tenaga professional di Sekolah Dasar Islam Terpadu (SD-IT) Hasanka Boarding School Palangkaraya dapat meningkatkan profesionalismenya. . Menambah pemahaman dan pengetahuan guru terhadap penyusun perangkat pembelajaran untuk kurikulum 2013 di SD-IT dan meningkatkan kemampuan guru dalam menyusun Perangkat pembelajarn kurikulum dengan tepat dan menerapkannya pada pembelajaran di SD-IT Hasankan Boarding School Palangka Raya, dan terdapat penyusunan perencanaan pelaksanaan pembelajaran yang sesuai dengan bidang studi mengacu pada kaidah kurikulum 2013 untuk diterapkan dalam pembelajaran di kelas. Kegiatan pengabdian ini menggunakan metode pengabdian dengan beberapa tahapan yaitu inkulturasi, discovery, desain define, dan refleksi. Hasil dari kegiatan ini adalah menghasilkan perangkat pembe;ajaran yang telah dibuat guru selama proses pelatihan dan pendampingan berupa Rencana Pelaksanaan Pembelajaran (RPP), Program Semester (Prosem) dan Program Tahunan (Prota) mengacu pada kaidah kurikulum 2013 dan dapat diimplementasikan pada kegiatan belajar mengajar di kelas masing-masing.